Rancang Bangun Alat Deteksi Penyimpangan Deformasi Bending di PT. X - Lubis, Muhammad Syafri; Sugeng, Margono (Bina Teknika, 2018)
PT. X is an automotive manufacturing that produce kind of any vehicle on Indonesia. Bending process is one of process system in PT. X. As the biggest manufacturing which have so many consument in Indonesia,  on time delivery is an important things that have to kept costumer smile achievement. From the main factor before if any proces that related delay delivery have to fastly contermeasure and standardization guarantee for reoccurance problem. With using 6 step Kaizen methode and focus to bending frame assy process and frame assy robot process that give the biggest impact to delivery, so as this reason the author make a target for both process can be guaranted as process delivery.